DEVELOPMENT OF A QUALIFICATION PROCEDURE FOR METHIONINE FORM OF INTERFERON ALFA-2b STANDARD TO CONFIRM ITS AUTHENTICITY BY MEANS OF A PEPTIDE MAPPING METHOD - O. B. Ustinnikova; E. O. Goloshchapova; O. B. Runova; M. G. Korotkov; R. A. Volkova (Медицинская иммунология)
Authenticity evaluation of proteins obtained with recombinant DNA technology is an important step in confirming efficacy and safety of the drugs based on them. One of the main ways to assess the authenticity is to compare molecular structure of the test and standard samples using the peptide mapping method with chromatographic separation of the products obtained by enzymatic degradation. Proper selection of a standard reference sample is essential in order to achieve reliable results. A standard sample of Interferon (CRS, Chemical Reference Substances) recommended by the European Agency for the Quality of Medicines for interferon alpha-2b substances containing N-terminal methionine is inappropriate, since the Interferon CRS sample doesn’t contain methionine. We present the results of development of qualification procedure for methionine form of Interferon alfa-2b industrial standard sample (ISS). The range of use for this ISS is authenticity confirmation for the methionine form of interferon alpha-2b substance using peptide mapping method with reverse-phase high-performance liquid chromatography (reverse-phase HPLC). The quality assessment was performed for all the parameters specified by the manufacturer of this candidate substance at the initial stage of qualification procedure, due to changed application area, and changed package size. Further, 30 peptide cards of the ISS candidate substance were obtained after pre-trypsinolysis of the protein followed by validated HPLC method with proven repeatability.It was shown that the hydrolysis conditions, i.e., the choice of trypsin preparations, may significantly affect the peptide map profile. Therefore, a reference to specific manufacturer and the catalog number of the product should be provided in description of application conditions for the ISS proposed.A set of eight reference peaks (peaks of comparison) has been justified, as based on evaluation of peptide maps and results of high-resolution mass spectrometry. The peak with maximally stable yield and intensity was selected as the main peak with an established absolute retention time. Two peaks with relative retention times were chosen as essential peaks for evaluation, i.e., the 1st peak containing N-terminal methionine, and the 2nd peak of highest molecular weight with an established amino acid sequence covering 11% of the studied interferon molecule.We have also qualified ISS parameters expressed as absolute (minimum for one reference peak), and relative (for the remaining reference peaks) retention time periods. Authenticity of the ISS candidate was further confirmed by the peptide mapping method, as compared with interferon CRS reference standard. Their peak patterns proved to be near-similar, except of a peak with eluted peptide containing N-terminal methionine as revealed by high-resolution mass spectrometry